Job Satisfaction Analysis of Managers at the Cooperative of Employees of the Republic of Indonesia Teachers and General Cicarimanah Sumedang - Reza Sopiana; Desan Henriawan (SINTESA, 2022)
The focus of this research is to analyze employee job satisfaction at the Indonesian Civil Servants Cooperative for Teachers and General Cicarimanah Sumedang. The purpose of this study was to determine how employee job satisfaction is and the efforts made to increase employee job satisfaction. The method used in this research is a qualitative method with employee productivity as the research variable. Research data collection is done through interviews, observation and documentation. The sampling technique uses purpose sampling. The research sample is the Indonesian Civil Servants Cooperative, Teachers and Public, Cicarimanah Sumedang. The research data was analyzed qualitatively using data collection, data reduction, data presentation and drawing conclusions. The results showed that the job satisfaction of employees at the Cooperative Employees of the Republic of Indonesia Teachers and General Cicarimanah Sumedang. already well. Then efforts to increase employee job satisfaction are by holding education and training, as well as providing work motivation so that they are always enthusiastic at work. Creating a good work climate with fellow employees and employees with their superiors so as to increase employee job satisfaction.